Orientasi keusahawanan, program pembangunan PKS dan kejayaan PKS di Perak - Nor Hafizah Hasan (Tanjong Malim, 2021)
Orientasi keusahawanan, program pembangunan PKS dan kejayaan PKS di Perak by Nor Hafizah Hasan